The histology of dermal glands of mating Breviceps with comments on their possible functional value in microhylids (Amphibia: Anura) - Visser, J. (1982)
During mating male and female Breviceps become ‘glued’ together. The distribution of multicellular dermal glands varies between the sexes. The mate has a large number of holocrine glands on the ventrum, while the female has similar glands on the dorsum of the back. II thus appears that both sexes contribute to the ‘glueing’ mechanism. New hypotheses to explain the adhesion between the sexes are proposed, viz., that the shift to terrestrial habils and subterranean laying in Breviceps have secondarily resulted in male si2e diminution. In other microhylids which adhere during aquatic oviposition, yet demonstrate a terrestrial morphology and habits, bouyancy is suggested to be of primary functional value.